2002
DOI: 10.1046/j.1365-4362.2002.01552_2.x
|View full text |Cite
|
Sign up to set email alerts
|

An interesting case of colocalization of segmental lichen planus and vitiligo in a 14‐year‐old boy

Abstract: A 14‐year‐old boy had segmental vitiligo (L3−4) on the right thigh and leg for 4 years, and was advised to apply topical clobetasol propionate, 0.05%, in the night, with daily sun exposure for 10 min, as he refused to comply with topical psoralens. As there was no response to therapy even after 3 months, the patient stopped the steroid cream but continued with the sun exposure. Subsequently, the patient noticed gradual‐onset, itchy, violaceous, pigmented, raised lesions superimposed on the vitiligo macules. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 6 publications
0
21
0
5
Order By: Relevance
“…Lichen planus (LP) has been previously associated with vitiligo [23,24,25,26,27,28,29,30,31]. Furthermore, some authorities consider FFA as a variant of LPP [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lichen planus (LP) has been previously associated with vitiligo [23,24,25,26,27,28,29,30,31]. Furthermore, some authorities consider FFA as a variant of LPP [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are several reports describing lesions of LP that developed mainly over sun-exposed vitiliginous skin [25,26,29,30,31]. Extrapolating this to FFA, actinic damage in vitiliginous skin may trigger initiation of FFA on vitiligo-affected skin.…”
Section: Discussionmentioning
confidence: 99%
“…A case of vitiligo developing around the lesions of LP is an example of this hypothesis [3] . Other evidence that suggests a possible common pathogenetic mechanism for the association of vitiligo and LP is colocalization of these disorders [6][7][8] .…”
Section: Commentmentioning
confidence: 99%
“…The last example of colocalized vitiligo and LP was a 14-yearold boy who developed LP lesions on the previous vitiligo lesions present for 4 years, which were located on both his legs [8] .…”
Section: Commentmentioning
confidence: 99%
“…Strict anatomical co-localization of psoriasis and lichen planus on lesions of VV have been reported in literature with hypothesis suggested by the authors. [6][7][8][9][10] Anstey et al and Sardana et al suggested that photodamage within the vitiliginous skin may alter the expression of antigens identified by infiltrating T cells in lichen planus. [9,10] Julian et al proposed that some cellular injury in vitiliginous skin might lead to immune mechanisms causing Koebner's phenomenon.…”
mentioning
confidence: 99%